2019
DOI: 10.1002/term.2836
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells are involved in early inflammation before macrophages in a rat adipose tissue engineering chamber model

Abstract: Adipose tissues regenerated using tissue engineering chambers (TECs) show the potential for applications in reconstruction of soft tissue defects. Previous studies have shown that early inflammation plays a key role in angiogenesis and adipogenesis required for adipose tissue generation. However, the sequence of events of the early inflammatory cascade is unclear. In this study, we investigated the role of early inflammatory cells in adipose tissue engineering using a rat TEC model. Rats in the TEC model were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
5
2
Order By: Relevance
“…Previous studies on fat mass and CD8 + T cells showed that mice with obesity had higher CD8 + T cells in adipose tissue (9,37). This increase in CD8 + T cell numbers in adipose tissue and blood has also been observed in adults and adolescents who are overweight or obese (12,15,(37)(38)(39).…”
Section: Previous Literature and Interpretationmentioning
confidence: 63%
See 3 more Smart Citations
“…Previous studies on fat mass and CD8 + T cells showed that mice with obesity had higher CD8 + T cells in adipose tissue (9,37). This increase in CD8 + T cell numbers in adipose tissue and blood has also been observed in adults and adolescents who are overweight or obese (12,15,(37)(38)(39).…”
Section: Previous Literature and Interpretationmentioning
confidence: 63%
“…The observed higher number of CD8 + T EM cells in our study and previous studies could be a direct effect of the increased fat mass. A previous study in adipose tissue of adults showed that CD8 + T cell infiltration, and especially the effector memory subset, might be the first immune cell appearance in adiposityinduced inflammation (9,38). The effector CD8 + T cells lack CCR7 expression and are able to directly migrate toward infected or inflamed tissues to execute their effector function (40).…”
Section: Previous Literature and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term post-implantation hematoma caused by lateral excursion of the subcutis on the relief CaP surface may play a key role in the vascularization and BMNC invasion required for enhanced tissue regeneration. The infiltration of adipose tissue by T cells peaked earlier than that by macrophages and resulted in the recruitment of additional infiltrating macrophages to enhance inflammation and the reconstruction of soft tissue defects [ 77 ]. Our data emphasize the significance of the T cell status for CaP implantation, which is not always successful at inducing subcutaneous vascularization and bone formation without osteogenic cells or bone growth factors [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%